Consumer’s demand for Disinfectants and Protective Gear from COVID-19 infection in Al-Hofuf, Saudi - Mohammed Al-Mahish; Noura AlDossari; Amal Almarri (Journal of Infection in Developing Countries)
Introduction: The paper aims to estimate consumers’ demand for personal protecting products (PPP) from COVID-19. Thus, the paper collected primary data on consumers’ demand for PPP utilizing the timeframe of the COVID-19 pandemic.